Fitness & wellness - Hoeger, Werner W. K.; Hoeger, Sharon A. (Cengage Learning, 2015)
Encourages students to start their path to fitness and wellness by providing coverage of core concepts, real life student case studies, and action steps to help students develop their own personal lifetime fitness and wellness program